AB0988 CLINICAL FEATURES AND ANALYSIS OF MEFV GENE IN 31 PATIENTS WITH FAMILIAL MEDITERRANEAN FEVER (FMF). (2nd June 2020) - Ishizuka, T.; Fujioka, K.; Tangiku, M.; Inui, S.; Tani, H.; Miwa, A.; Ikeda, T.; Taguchi, K.; Morita, H.; Toma, T.; Yachie, A.
Abstract : Background: FMF is recessive systemic autoinflammatory disorder characterized by recurrent fever, peritonitis, pleuritis, pericarditis and arthritis accompanied with headache and abdominal pain. Mutation of MEFV gene encoding pyrin resulted in inflammasome activation and the uncontrolled production of IL-1β. Overview of pathogenesis, clinical features and management in Japanese patients with FMF had been reported. However, the differences of clinical features between mutated and non-mutated of MEFV still remain unclear. Objectives: We have analyzed 31 Japanese patients with FMF in Gifu district to clarify the association between various clinical features and mutation of MEFV. Methods: Genomic DNA were purified from white blood cells in 31 FMF patients, and mutated MEFV has been explored. We have analyzed MEFV, TNFRSF1A, MVK and NLRP3 genes in 31 patients with FMF except for 1 patient. Therefore, we excluded another autoinflammatory diseases such as TNF receptor-associated syndrome (TRAPS), mevalonate kinase deficiency and cryopyrin-associated periodic syndrome. Clinical symptoms and laboratory data were analyzed around onset time. Each patient had been treated with colchicine (0.5-2 mg). Results: Characteristics of Patients with FMF (22 female/9 male) were as follows; Onset time were 0-56 years-old (21.4 ±11.8), and Frequencies of clinical symptoms such as periodic fever, headache, abdominal pain, arthralgia, chest pain, cervical lymph nodes swelling, and myalgia were 31/31, 9/31, 8/31, 6/31, 5/31, 3/31 and 1/31, respectively (double symptoms were observed). Patients with FMF were divided into 3 groups as follows; Patients with typical compound heterozygous mutations of MEFV (E148Q /M694I) which indicated exon 10 mutation, were 5 cases (G1). Patients with atypical mutations, except for exon 10, such as 133G>A in 3UTR, exon 1 (E84K), 2 (L110P, E148Q), 3(R202Q, P257L, G304R, P369S, R408Q), 5(S503C) and 9(I591M) were 13 cases (G2). Patients with no mutations in MEFV gene were 12 cases (G3). There were no significant differences of age at first visiting hospital (FV)and onset age of fever attack (O) (FV: 29.0 ± 15.6, 27.1 ± 12.5 years-old (yo) and 34.7 ± 12.7 yo, O: 21.0 ± 17.6 yo, 17.8 ± 12.1 yo and 25.2 ± 6.5). But significant differences in duration of fever attack (D) and frequency of fever attack (FF) between G1 and G2 or G3 were observed as follows; (D: 2.2 ± 0.4 days vs 5.5 ± 3.1 days, P<0.05, and 3.8 ± 1.7 days), FF: 0.72 ± 0.3/month (M), 1.24 ± 1.1/M, and 1.5 ± 0.7/M vs group1, P<0.05), respectively. Laboratory examinations such as WBC, CRP and serum amyloid A (SAA)at fever attack were not significantly different between 3 groups. All of those patients were effective for colchicine treatment except for 2 patients in group 1 because of loss of hair, severe diarrhea and liver dysfunction due to side effects of colchicine. Finally, 4 patients in G1and G2 received canakinumab treatment. Patients with MEFV mutations have no family histories. Mutations of E148Q were found in 12 patients (40%). Conclusion: We have examined association between clinical features and mutations of MEFV in 31 patients in Gifu district, suggesting that duration of fever attacks and frequency of fever attacks in G1 are significantly shorter than G2 and G3, respectively in Japanese patients with FMF. Mutations of E148Q in exon 2 were observed in 16-23 % of normal Japanese patients, indicating that E148Q is the polymorphism or accelerating factor. Disclosure of Interests: None declared